Women and Money: Unique Issues – Money Issues Across the Life Cycle - Diann Douglas; Martie Gillen; Lynda Spence (EDIS, 2013)
Most families depend on a woman’s income to help support the household. Some women are co-breadwinners while others are the only source of income. Throughout a woman’s life, she will experience many money issues unique to women. A woman may experience the following situations: lower earnings, a longer life expectancy, lack of retirement planning, divorce, and fewer years in the workplace because of childrearing or caring for older parents. Many of these issues can work against a woman’s ability to accumulate money and attain stable financial status. This 3-page fact sheet was written by Diann Douglas, Martie Gillen, and Lynda Spence, and published by the UF Department of Family Youth and Community Sciences, March 2013.